Design para bem-estar: educação financeira para pessoas surdas - Santos, Rodrigo dos (Universidade do Vale do Rio dos Sinos, 2025)
A Product-Service System (PSS) is related to innovation strategies that aim to shift the focus of businesses from designing and selling only physical products to doing the same from a system of products and services that are suited to meet specific customer demands. This thesis proposed the construction of a PPS in the environment of financial institutions in Brazil, supported by the National Strategy for Financial Education (ENEF), for deaf people. Using design as the basis for promoting well-being for the research target audience, this Thesis contextualized financial education under the ENEF in the country and the responsibility of financial institutions in promoting inclusive and accessible information for their customers. The research was carried out in stages, starting with a quantitative phase with the application of two research instruments (consumer wisdom and perceived financial well-being scales), back-translated into Libras, followed by qualitative research with the application of 6 in-depth interviews, a project workshop and a final experiment to validate the guidelines. As methodological support for further research, analogous cases that provide services to deaf people were explored, such as an American coffee shop and a Brazilian ice cream shop, as well as a finance education company and an association of financial market entities. The experiment to validate the guidelines simulated banking services for deaf people in Libras, using two artifacts (brochures with information on banking products) developed in Portuguese and Libras for this research. The research demonstrated that an SPS built with full support for Brazilian Sign Language (Libras) tends to provide greater well-being for the deaf public in matters related to financial education and proved the importance and essentiality of the participation of the deaf public in the design process.
Keywords: Design para bem-estar; Educação financeira; Pessoas surdas; Experiência; Inclusão; Design for well-being; Financial education; Deaf people; Experience; Inclusion; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial